Progression of the first stage of labour, in low risk nulliparas in a South Asian population: a prospective observational study. (17th November 2021) - Purwar, Roli; Malik, Sunita; Khanam, Zeba; Mishra, Archana
Abstract: We compared the labour pattern in the active phase of labour, defined at 4 cm versus 6 cm cervical dilatation, in a South Asian population. This was a prospective observational study where 500 low risk nulliparous women were recruited. Our aim was to study, the average labour pattern curve of all parturients. Mean duration of the active phase from 4 to 10 cm was 5.12 ± 2.10 hours and from 6 to 10 cm was 2.79 ± 1.72 hours. The 95th percentile values suggests that it takes 5–6 hours to progress from 4 to 6 cm and again 5–6 hours from 6 to 10 cm. The minimum labour progression rate can be as low as 0.5 cm/hour with vaginal delivery (VD) still being achieved. The slope of labour curve steepens after 6 cm, suggesting 6 cm as the onset of the active phase. Allowing labour to continue for a longer period before 6 cm of cervical dilation may reduce the rate of unnecessary intrapartum intervention and caesarean section (CS) for labour dystocia. Impact Statement: What is already known on this subject ? Friedman's definitions of normal labour and abnormal labour are widely accepted in current obstetric practises. Friedman's normal dilatation rate of 1 cm/h that is universally accepted is becoming questionable in our current obstetric population because of escalating rates of unnecessary labour interventions like oxytocin augmentation and CS. What the results of this study add ? The rule of 1 cm/hour of labour progression cannot be applied to every woman and inappropriate interventions should be withheld until labour progression does falls below 0.5 cm/hour. What the implications are of these findings for clinical practice and/or further research? Six centimetres rather than 4 cm of cervical dilatation is a more appropriate landmark for the start of the active phase. Allowing labour to continue for a longer period before 6 cm of cervical dilation may reduce the rate of unnecessary intrapartum interventions and CS for labour dystocia.